Juridical Analysis of the Imposition of Value Added Tax (VAT) on Foreign Digital Products - Khairiah Nasution; Zhafira Maliha; Sandrina Aika Humaira; Nayla Aulia Rangkuti; Nabilah Putri Ayuni (ISNU Nine-Star Multidisciplinary Journal, 2025)
The development of digital technology has opened up new economic opportunities, including in terms of the use of foreign digital products by the Indonesian people. Products such as streaming services, digital applications, and software are now part of daily needs, but often come from overseas providers who do not have a physical presence in Indonesia. This poses challenges for the national tax system, especially in the imposition of Value Added Tax (VAT). This study aims to analyze the legal basis for the imposition of VAT on foreign digital products based on the prevailing laws and regulations in Indonesia. The research method used is normative juridical with a legislative and literature study approach. The results of the study show that the imposition of VAT on foreign digital products has been regulated in Law Number 42 of 2009 and strengthened by derivative regulations such as the Regulation of the Minister of Finance. The implementation of this policy is important to create fiscal justice between domestic and foreign business actors. However, the effectiveness of this policy still requires improvement in technical aspects and supervision. This study concludes that the legal approach to digital taxes must be continuously updated to be in line with global economic dynamics.